Diagnostic Value of GSTP1, RASSF1, AND RASSF2 Methylation in Serum of Prostate Cancer Patients: Genetic markers in prostate cancer - Aykanli, Emre; Arisan, Serdar; Arisan, Elif Damla; Yavuzsan, Abdullah Hizir (Urology Journal, 2024)
Purpose: Considering the inadequacy of PSA measurement in the diagnosis of prostate cancer, it is aimed to establish a potential liquid biopsy diagnostic panel. Materials and Methods: 39 patients who underwent TRUS-biopsy and 15 healthy volunteers were included. Approximately 15 ml of venous blood samples taken from healthy volunteers and patients before biopsy were separated as plasma. Hypermethylation status of GSTP1 and RASSF1:RASSF2 genes was revealed in cfDNA materials collected from plasma samples. Correlation of this epigenetic change detected in PCa, BPH and healthy volunteer groups with pathology results was examined. Results: Pathology reports of 39 patients included were 13 PCa, 3 ASAP, 3 HGPIN, and 20 BPH. In total, 3 of the patients with PCa had positive GSTP1, 4 had RASSF1 and 9 had positive RASSF2 methylation. It was seen that RASSF2 had the highest sensitivity (69%), specificity (39%) and NPV (80%), while RASSF1 had the highest PPV (30%). When the binary combinations of genes were examined it was observed that the GSTP1:RASSF1 combination had the highest sensitivity (46%), specificity (76%) and NPV (82%). When the methylation of all three genes was examined, it was observed that the sensitivity was quite low (8%), but the specificity (83%) increased significantly. Conclusion: Although we observed that the GSTP1 and RASSF1 methylation positivity rates that we examined in our study were higher in patients without prostate cancer, we found that the RASSF2 methylation rate was higher in patients with prostate cancer. randomized controlled studies are needed.